Hybrid Converter to Supply DC and AC Loads Using Tapped Boost Topology - Menon, Goutham; Ratheesh, Mahesh; S Menon, Gopikrishna; S, Gautham; Kanakasabapathy, P (International Journal of Engineering and Technology, 2018)
Advancements in power electronic systems has brought forth the modernization of residential power systems exponentially. The interfacing of AC and DC loads with various kinds of resources of energy has been achieved with the help of modern nanogrid architectures. This paper brings into depiction a Tapped Boost derived hybrid converter that can be used to meet the demands of both AC and DC loads having a solitary DC input. A voltage source inverter (VSI) bridge network is used instead of the single switch of a Tapped Boost converter. The VSI bridge has shoot-through protection in the inverter stage increasing its importance for smart power systems. The Tapped Boost derived converter also borrows the advantages provided by the Tapped Boost converter. The paper covers topics like the operation, steady-state analysis and operating modes of the proposed Tapped Boost-DHC. The output and input characteristics has also been tested and verified through simulatio